SIX1 mutations cause branchio-oto-renal syndrome by disruption of EYA1–SIX1–DNA complexes - Ruf, Rainer G. (National Academy of Sciences, 2004)
Urinary tract malformations constitute the most frequent cause of chronic renal failure in the first two decades of life. Branchio-otic (BO) syndrome is an autosomal dominant developmental disorder characterized by hearing loss. In branchio-oto-renal (BOR) syndrome, malformations of the kidney or urinary tract are associated. Haploinsufficiency for the human gene EYA1, a homologue of the Drosophila gene eyes absent (eya), causes BOR and BO syndromes. We recently mapped a locus for BOR/BO syndrome (BOS3) to human chromosome 14q23.1. Within the 33-megabase critical genetic interval, we located the SIX1, SIX4, and SIX6 genes, which act within a genetic network of EYA and PAX genes to regulate organogenesis. These genes, therefore, represented excellent candidate genes for BOS3. By direct sequencing of exons, we identified three different SIX1 mutations in four BOR/BO kindreds, thus identifying SIX1 as a gene causing BOR and BO syndromes. To elucidate how these mutations cause disease, we analyzed the functional role of these SIX1 mutations with respect to protein–protein and protein–DNA interactions. We demonstrate that all three mutations are crucial for Eya1–Six1 interaction, and the two mutations within the homeodomain region are essential for specific Six1–DNA binding. Identification of SIX1 mutations as causing BOR/BO offers insights into the molecular basis of otic and renal developmental diseases in humans.